Mahasiswa Kukerta UNRI Mengadakan Sosialisasi Dan Pembuatan Lilin Aromaterapi Dari Limbah Minyak Jelantah - Daffeta Fitrilinda; Angelina Agatha Hutabalian; Berliana Effendi; Edi Kurniawan; Hediyanti Putri; Khoirunnisa Tri Wulandari; Mikhael Suryadinata Manurung; Naura Hana Avifa; Pita Siallagan; Rangga Christian; Yohana Cecilia (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2023)
Waste cooking oil becomes a health problem if consumed and causes damage to natural ecosystems if it is thrown into the environment. Utilizing used cooking oil waste into aromatherapy candles is an appropriate alternative. The aim of this activity is to reduce waste and increase the creativity of Family Empowerment and Welfare (PKK) women to create superior regional products. This activity consists of four stages, namely creation, testing, socialization, and experimental demonstration. The result of this activity is that it can provide change in the form of the emergence of an initiative by PKK women to produce products that have sales value and have benefits.